Hipertensão arterial na Ilha do Governador, Rio de Janeiro, Brasil: I. Metodologia - Klein, Carlos Henrique (1995)
The aim of this paper (first of a series of two) is to present the main methodological aspects used in a cross-sectional study whose proposals were to establish the prevalence of arterial hypertension in adults in Ilha do Governador (a district of the city of Rio de Janeiro, Brazil), and to examine its relationship to other risk factors, including those for cardiovascular diseases, so as to establish its control status. Sampling design (of clusters in strata, according to mean household income) is described in detail, in addition to measurement methods, and training of observers. Indicators of performance in field work and quality control are also presented as results of the application of the metodology of study.